2001
DOI: 10.1074/jbc.m105075200
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of an IMP Dehydrogenase Gene and Its Overexpression in Drug-sensitive Transcription Elongation Mutants of Yeast

Abstract: IMP dehydrogenase is a rate-limiting enzyme involved in the synthesis of GTP. In mammalian cells it is regulated with respect to growth rate and is the target of numerous therapeutic agents. Mutations in the RNA polymerase II elongation machinery render yeast sensitive to inhibitors of IMP dehydrogenase and defective in inducing transcription of one of the IMP dehydrogenase-encoding genes, IMD2. Here we show that loss of IMD2, but not IMD1, IMD3, or IMD4, conferred upon yeast the same drug sensitivity found in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
86
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(94 citation statements)
references
References 50 publications
(70 reference statements)
8
86
0
Order By: Relevance
“…5C) [although inhibition of overall transcription is a consequence of lowering intracellular NTP levels (27), we do not yet know whether this RNA is more inhibited than the average RNA by 6AU]. In contrast, the IMD2 mRNA is readily induced in wild-type cells (31), and this does not require Rrp6p (Fig. 5C).…”
Section: A New Class Of Rna Transcripts With An Uncertain Relationshimentioning
confidence: 93%
“…5C) [although inhibition of overall transcription is a consequence of lowering intracellular NTP levels (27), we do not yet know whether this RNA is more inhibited than the average RNA by 6AU]. In contrast, the IMD2 mRNA is readily induced in wild-type cells (31), and this does not require Rrp6p (Fig. 5C).…”
Section: A New Class Of Rna Transcripts With An Uncertain Relationshimentioning
confidence: 93%
“…In contrast, inhibitors of IMPDH activity, such as mycophenolic acid (MPA) or 6-azauracil (6AU) that lower GTP pools (Exinger and Lacroute 1992) 2003b; Kuehner and Brow 2008). A repressive element was also identified between the TATA box and the transcriptional start site (Shaw et al 2001) and was shown to have transcription terminator properties (Jenks et al 2008).…”
Section: Regulation Of Gtp Synthesismentioning
confidence: 99%
“…Interestingly, in Bacillus subtilis, diminution of intracellular GTP concentration is required for proper entry into stationary phase (Ratnayake-Lecamwasam et al 2001). In yeast, expression of IMPDH-coding genes (IMDs) is strongly affected by growth phase (Shaw et al 2001;Escobar-Henriques et al 2003a). A mutagenesis of the IMD2 gene revealed that the sequence involved in growth phase regulation lies in the coding region of the gene (Escobar-Henriques et al 2003a).…”
Section: Nucleotide Balancementioning
confidence: 99%
“…The GTP level is closely linked to ppGpp synthesis because (1) ppGpp synthesis consumes GTP as a substrate, and (2) ppGpp potently blocks GTP synthesis by inhibiting IMP dehydrogenase activity. The first effect (consumption of (Shaw et al, 2001). As ppGpp did not inhibit the IMP dehydrogenase activity of S. cerevisiae (Table 2), eukaryotic IMP dehydrogenases may be insensitive to ppGpp.…”
Section: Discussionmentioning
confidence: 99%
“…In mammalian cells, IMP dehydrogenase is a rate-limiting enzyme involved in de novo GTP biosynthesis. Therefore, we examined whether ppGpp inhibits yeast IMP dehydrogenases, which are present as four isozymes (IMD 1-4 encoded by YAR073W, YHR216W, YLR432W and YML056C, respectively) (Shaw et al, 2001). IMD1 is an inactive pseudogene.…”
Section: Ppgpp Does Not Inhibit Yeast Imp Dehydrogenase Activitymentioning
confidence: 99%